2020
DOI: 10.1111/ele.13497
|View full text |Cite
|
Sign up to set email alerts
|

Plant community composition steers grassland vegetation via soil legacy effects

Abstract: Soil legacy effects are commonly highlighted as drivers of plant community dynamics and species co-existence. However, experimental evidence for soil legacy effects of conditioning plant communities on responding plant communities under natural conditions is lacking. We conditioned 192 grassland plots using six different plant communities with different ratios of grasses and forbs and for different durations. Soil microbial legacies were evident for soil fungi, but not for soil bacteria, while soil abiotic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
98
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 54 publications
11
98
0
1
Order By: Relevance
“…This observation is consistent with previous studies showing that forbs tend to grow better with grasses than with other forbs (Cahill et al, 2008), or that forbs grow better with heterospecifics than conspecifics (Semchenko et al, 2013). This is also consistent with PSF experiments showing that forbs grow better on soil conditioned by grasses than on soil conditioned by other forbs (Hendriks et al, 2013;Heinen et al, 2020). Based on recent evidence suggesting that plants with lower SRL are better at tolerating interspecific competition (Semchenko et al, 2018) and may be better able to cope with nitrogen stress (Freschet et al, 2018), we hypothesise that the production of roots with a lower SRL by D. deltoides is probably a plastic response that may increase plant fitness in the presence of grass competitors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with previous studies showing that forbs tend to grow better with grasses than with other forbs (Cahill et al, 2008), or that forbs grow better with heterospecifics than conspecifics (Semchenko et al, 2013). This is also consistent with PSF experiments showing that forbs grow better on soil conditioned by grasses than on soil conditioned by other forbs (Hendriks et al, 2013;Heinen et al, 2020). Based on recent evidence suggesting that plants with lower SRL are better at tolerating interspecific competition (Semchenko et al, 2018) and may be better able to cope with nitrogen stress (Freschet et al, 2018), we hypothesise that the production of roots with a lower SRL by D. deltoides is probably a plastic response that may increase plant fitness in the presence of grass competitors.…”
Section: Discussionsupporting
confidence: 92%
“…arrive early at a site, they will alter the biotic and abiotic components of the soil environment and create soil legacies that might affect early species performance (often negatively) as well as the growth and development of species arriving later during succession (Klironomos, 2002;Bever, 2003;Grman and Suding, 2010). Previous studies showed that early-arriving species can induce soil legacy effects through changes in the composition of soil microbial communities (e.g., accumulation of pathogenic fungi), which can then contribute to historical contingency effects by altering competitive relationships in plant communities (Kardol et al, 2007;Heinen et al, 2020). However, due to the strong interlinkage between microbial communities living in the rhizosphere and metabolites exuded by plant roots, biotic PSF effects are tightly associated with root exudation (Mommer et al, 2016;Sasse et al, 2018;Korenblum et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Averages ± SE are shown; n = 8 [Colour figure can be viewed at wileyonlinelibrary.com] expectations based on controlled experiments ( Figure 6A,C), indicating that also the direction of these effects would need to change through time. Moreover, Heinen et al (2020) showed that fungal pathogens may also decrease over time. Long-term experiments have to determine how soil legacy effects change through time and how short-term greenhouse estimates represent (semi-)field soil legacy effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 'current forb' soils with a legacy of previous grasses on them had very different fungal communities than 'current forb' soils with a legacy of previous forbs. Other work has shown that plant family and functional group can explain a large portion of the variation in fungal community structure (31,40,41) and that this division may play a prominent role in plant community dynamics in natural grasslands (7,42). This is likely due to species in these groups having higher similarities within than between groups in terms of functional traits (43,44) and chemical composition (45,46), which play an important role in shaping soil legacies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with the conceptual idea that fungal growth rates are slower than those of bacteria (34,35) and that because of this, fungi are more stable and less affected by for instance temporal variability in the habitat or environment (31). Importantly, the more persistent effects of plants on the soil fungal communities than on bacterial communities may explain why most correlative studies that link plant responses and changes in the soil microbiome have shown that fungal communities drive plant community dynamics, while bacteria do not seem to strongly influence plant-soil-feedbacks (7,36) despite their known importance in rhizosphere processes (1,10). This is potentially due to faster turnover times of soil bacterial communities (34).…”
Section: Discussionmentioning
confidence: 99%